The Oxford handbook of American literary realism - Newlin, Keith 1956- (Oxford University Press, 2019)
"The Oxford Handbook of American Literary Realism offers 35 original essays of fresh interpretations of the artistic and political challenges of representing life accurately. Organized by topic and theme, essays draw upon recent scholarship in literary and cultural studies to offer an authoritative and in-depth reassessment of major and minor figures and the contexts that shaped their work. One set of essays explores realism's genesis and its connection to previous and subsequent movements. Others examine the inclusiveness of representation, the circulation of texts, and the aesthetic representation of science, time, space, and the subjects of medicine, the New Woman, and the middle class. Still others trace the connection to other arts--poetry, drama, illustration, photography, painting, and film--and to pedagogic issues in the teaching of realism"--